How to activate a place - Veras, Eduardo (PORTO ARTE: Revista de Artes Visuais, 2019)
Abstract Through critical analysis of the work of Quintino (2002), by Jailton Moreira (São Leopoldo, 1960), this article studies aspects of the relationship between art and memory. It discusses, initially, the efficacy of the artistic creation in bereavement works (art as coping mechanism of a loss), and, afterwards, it observes how the piece of art aims to juxtapose the notions of time and space, place and memory. In essence, it debates the game played between the dear oblivion inherent to urban life – what the city dynamics eliminates, buries, and denies – and what family remembrance refuses to set aside. Resumo A partir do exame crítico de Quintino (2002), de Jailton Moreira (São Leopoldo, 1960), o presente trabalho investiga aspectos das relações entre arte e memória. Discute inicialmente a eficácia da criação artística no trabalho de luto (a arte como elaboração de uma perda) e, na sequência, observa como a referida peça logra justapor as noções de espaço e tempo, lugar e memória. No cerne, debate-se o jogo armado entre os esquecimentos caros à vida urbana – o que a dinâmica da cidade elimina, soterra e renega – e o que a rememoração familiar se recusa a deixar de lado.